A simple design of vibration sensor using fiber optic displacement sensor - Yasin, M.; Harun, Sulaiman Wadi; Kusminarto, D.; Ahmad, Harith (National Institute of Optoelectronics, 2010)
A simple design of vibration sensor is proposed and demonstrated using fiber optic displacement sensor based on intensity modulation technique. The maximum sensor output voltage obtained is 1.65 mV for a distance of 1.2 mm between the reflective surface and the fiber optic probe. The sensitivity of the sensor is found to be 0.0029 mV/mu m over 325 to 650 mu m range and -0.0005 mV/mu m over 1300 mu m to 3500 mu m range. The sensor is capable of measuring vibration amplitude ranging from 0.22 mm to 0.44 mm within a frequency range of 200 to 350 Hz. The simplicity of the design, high degree of sensitivity, dynamic range and the low cost of the fabrication make it suitable for real field applications.